Management of late adolescent privacy communications to step-parents - Kartika, Risma; Qodriyah, Shafira Sholihatul (Bricolage : Jurnal Magister Ilmu Komunikasi, 2023)
Families with stepparents are common in Indonesia and are not considered taboo by society. The relationship between late adolescents and stepparents in a family environment will show different quality of communication, however the delivery of personal information in an interaction can affect the relationship between the two. Communication Privacy Management (CPM) which focuses on individual management in processing their privacy, which is reviewed from 5 elements, namely, Private Information, Privacy Boundaries, Control and Ownership, Rule-Based Management and Privacy. Management Dialectics. This study looked at how late adolescents manage their personal communication management in establishing relationships with their stepparents. This study uses qualitative methods and forms a description of the data observed by the researcher. The results of this research indicate that the decision to choose to disclose and not to disclose personal information is based on existing privacy limitations, the more intimacy is attached to the relationship, the smaller the privacy barrier. However, there is intimacy between late adolescence and stepparent, late adolescence still has hidden information that is not disclosed.